Creative soft Furnishings - Rapley, Sylvia (London Hamlyn, 1997)
A HAMLYN GUIDE TO CREATING YOUR HOME series guide to projects using fabric to decorate and improve the home. A techniques section explains fabric stencilling, patchwork, canvaswork, making rosettes and tassels and using ribbons and braids.
Include Colored Illustration, Indexes
Covered Design By Senate
Keywords: House furnishings -- Handicraft -- Textile fabrics in interior decoration